Liposomal melatonin rescues methamphetamine‐elicited mitochondrial burdens, pro‐apoptosis, and dopaminergic degeneration through the inhibition PKCδ gene. Issue 1 (2nd December 2014) - Nguyen, Xuan‐Khanh Thi; Lee, Jaehwi; Shin, Eun‐Joo; Dang, Duy‐Khanh; Jeong, Ji Hoon; Nguyen, Thuy‐Ty Lan; Nam, Yunsung; Cho, Hyun‐Jong; Lee, Jae‐Chul; Park, Dae Hun; Jang, Choon‐Gon; Hong, Jau‐Shyong; et al.
Abstract We have demonstrated that mitochondrial oxidative damage and PKCδ overexpression contribute to methamphetamine‐induced dopaminergic degeneration. Although it is recognized that antioxidant melatonin is effective in preventing neurotoxicity induced by methamphetamine, its precise mechanism remains elusive. C57BL/6J wild‐type mice exhibited a similar degree of dopaminergic deficit when methamphetamine was administered during light and dark phases. Furthermore, dopaminergic neuroprotection by genetic inhibition of PKCδ during the light phase was comparable to that during the dark phase. Thus, we have focused on the light phase to examine whether melatonin modulates PKCδ‐mediated neurotoxic signaling after multiple high doses of methamphetamine. To enhance the bioavailability of melatonin, we applied liposomal melatonin. Treatment with methamphetamine resulted in hyperthermia, mitochondrial translocation of PKCδ, oxidative damage (mitochondria > cytosol), mitochondrial dysfunction, pro‐apoptotic changes, ultrastructural mitochondrial degeneration, dopaminergic degeneration, and behavioral impairment in wild‐type mice. Treatment with liposomal melatonin resulted in a dose‐dependent attenuation against degenerative changes induced by methamphetamine in wild‐type mice. Attenuation by liposomal melatonin might be comparable to that by genetic inhibition (using PKCδ(−/−) mice or PKCδ antisense oligonucleotide). However, liposomal melatonin did not show any additional protective effects on the attenuation by genetic inhibition of PKCδ. Our results suggest that the circadian cycle cannot be a key factor in modulating methamphetamine toxicity under the current experimental condition and that PKCδ is one of the critical target genes for melatonin‐mediated protective effects against mitochondrial burdens (dysfunction), oxidative stress, pro‐apoptosis, and dopaminergic degeneration induced by methamphetamine.